IMPLEMENTASI CARA HIDUP JEMAAT KRISTEN PERDANA DALAM PERSEKUTUAN DOA ORANG MUDA PEMBAHARUAN KARISMATIK KATOLIK (PDOMPKK) - Sari, Paskalia Agatha Vinindya; Dadi, Kanisius Komsiah (CREDENDUM: Jurnal Pendidikan Agama, 2023)
The Catholic Charismatic Renewal Prayer Fellowship is a movement that encourages a more profound Christian faith experience within the Indonesian Catholic Church. Despite the hierarchy's support, concerns have been raised regarding this movement's theological alignment and prayer practices with traditional Catholic teachings. This research aims to investigate the Youth Catholic Charismatic Renewal Prayer Fellowship of St. Maria-Tangerang Parish, focusing on their spiritual foundation and efforts to align with Catholic traditions. Utilizing a descriptive qualitative method, this study relies on interviews and direct observations conducted with the administrators and members of the Youth Catholic Charismatic Renewal Prayer Fellowship. The findings indicate that the group's prayer activities are rooted in the spirit of The First Christian Church while maintaining consistency with Catholic traditions such as the Rosary Prayer. The analysis concludes that the biblical, theological, and traditional foundations of the Youth Catholic Charismatic Renewal Prayer Fellowship in the Tangerang Parish are Catholic teachings.